Five studies evaluating the impact on mental health and mood of recalling, reading, and discussing fiction - Carney, James; Robertson, Cole (PLOS ONE, 2022)
Does reading fiction improve mental health and well-being? We present the results of five studies that evaluated the impact of five forms of exposure to fiction. These included the effects of recalling reading fiction, of being prescribed fiction, of discussing fiction relative to non-fiction, and of discussing literary fiction relative to best-seller fiction. The first three studies directly recruited participants; the final two relied on scraped social media data from Reddit and Twitter. Results show that fiction can have a positive impact on measures of mood and emotion, but that a process of mnemonic or cognitive consolidation is required first: exposure to fiction does not, on its own, have an immediate impact on well-being.